Estudio de la viabilidad para exportar desde el Tolima - Ibagué a países bajos carne de Codorniz (2021)
The present work aims to study the viability of exporting quail meat from Tolima to the Netherlands, based on the nutritional benefits that this meat offers and the environmental conditions that Colombia has to carry out the production and commercialization of these birds. The development of coturniculture and the poultry industry, has been immersed in times of crisis, due to unplanned production, incorrect management in production and marketing processes, unfair competition, oversupply, sanitary problems and non-compliance with the regulations for the improper compliance of the process while it is being carried out, which is why it begins by analyzing the productive sector of Tolima which reflects that it is one of the departments of Colombia that contributes the least to PIB, the coturnicola sector is a strong sector that requires more incentive and support from the National Federación Nacional de Avicultores de Colombia (FENAVI) and Ministerio de Agricultura y Desarrollo Rural, development, this in turn would create more jobs. It is observed that in Colombia the consumption of this meat is little taking the determination to look for alternative markets having as objectives restaurants, hospitals, neighborhood stores, supermarkets, supermarkets.